NiO/ZnO Nanowire-heterostructures by Vapor Phase Growth for Gas Sensing. (2016) - Kaur, Navpreet; Comini, Elisabetta; Poli, Nicola; Zappa, Dario; Sberveglieri, Giorgio
Abstract: Physical interface between p and n-types semiconducting materials known as p-n junction or heterojunction represents the key technology in many electronic and optoelectronic devices such as gas sensors. In this work we are presenting a novel method for the growth of NiO/ZnO (NWs) based heterostructures with vapor phase mechanism and their preliminary sensing study for acetone. To fabricate the NiO/ZnO NWs heterostructures, firstly NiO nanowires were grown on alumina substrates with Vapor-Liquid-Solid (VLS) method and then Vapor-Solid (VS) method was used for the growth of ZnO nanowires on as grown NiO nanowires. The surface morphology of NiO nanowires and NiO/ZnO heterostructures were investigated with scanning electron microscopy (FE-SEM). Raman spectroscopy has also been used for the structural characterization of heterostructures. A set of conductromertric sensing devices based on NiO/ZnO heterostructures have been prepared. The preliminary sensing performance of NiO/ZnO NWs heterostructure devices towards acetone at temperature of 400°C is reported in this work.